The deepest well : healing the long-term effects of childhood adversity - Burke Harris, Nadine, 1975- (Boston : Houghton Mifflin Harcourt, 2018)
A pioneering physician reveals how childhood stress leads to lifelong health problems and what we can do to break the cycle. For anyone who has faced a difficult childhood, or who cares about the millions of children who do, the innovative and acclaimed health interventions outlined in this book will represent vitally important hope for change.--
Discovery. Something's just not right -- To go forward, go back -- Forty pounds -- Diagnosis. The drive-by and the bear -- Dynamic disruption -- Lick your pups! -- Prescription. The ACE antidote -- Stop the massacre! -- Sexiest man alive -- Maximum-strength bufferin' -- Revolution. The rising tide -- Listerine -- In the rearview -- Epilogue -- Appendix 1: What's my ACE score? -- Appendix 2: CYW Adverse Childhood Experiences Questionnaire.
Includes bibliographical references (pages 235-242) and index.
Keywords: Psychic trauma in children -- Complications; Post-traumatic stress disorder in children -- Complications; Adult child abuse victims -- Health and hygiene; Stress, Psychological; Stress Disorders, Post-Traumatic.; Child; Child Abuse; Adult child abuse victims -- Health and hygiene; FAMILY & RELATIONSHIPS / Abuse / Child Abuse; FAMILY & RELATIONSHIPS / Life Stages / Infants & Toddlers; HEALTH & FITNESS; PSYCHOLOGY / Developmental / Child; SCIENCE / Life Sciences / Human Anatomy & Physiology; SELF-HELP.; SOCIAL SCIENCE / Children's Studies